Association between Sociodemographic and Health Behaviours with Body Weight Status among Adults in Terengganu, Malaysia - Zamani, Nur Na’imah Fatimah; Mohd Habir, Mohamad Wafiq; Mohd Noor, Siti Maisarah; Roslim, Nurul Afiedia; Ahmad, Aryati (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
This study aimed to determine the association between sociodemographic and health behaviours with body weight status among adults with healthy weight and overweight/obese in Terengganu. This cross-sectional study involved the measurement of body weight and height, followed by the categorization of BMI. Sociodemographic and health behaviour information was obtained through questionnaires, covering variables such as education level, monthly income, locality, gender, age, race, sleep quality, eating behaviours, and physical activity. A total of 326 adults with healthy weight (44.2%) and overweight/obesity (55.8%) in Terengganu aged 19‒60 years old were recruited. There were significant associations between age (p<0.001), gender (p<0.001), race (p=0.008), education level (p<0.001) and eating behaviour (p=0.012) with body weight status. These findings emphasize the impacts of sociodemographic factors and health behaviours in understanding and addressing the issue of overweight and obesity and will be used as a basis for developing effective and targeted intervention programs.